Efforts to Improve Sprint Running Learning Outcomes Through Play Models for Class V Students at State Elementary School 024869 South Binjai - Tanjung, Muhammad Nasir; Syaleh, Muhammad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research aims to determine the improvement in sprint learning outcomes for class V students through the playing method at SD Negeri 024869 Binjai Selatan for the 2023/2024 academic year. This research is classroom action research (PTK). This research was carried out in two cycles, with each cycle consisting of planning, implementing actions, observing and reflecting. The data source in this research is the results of student tests in the form of sprint running applications. Data collection techniques by assessing sprint learning outcomes. The data analysis technique used in this research is descriptive based on qualitative analysis with percentages. Based on the research results, the following conclusions can be drawn: (1) Through the play model, it is very good to improve sprint learning outcomes for class V students at SD Negeri 024869 South Binjai for the 2023/2024 academic year. From the analysis, a significant improvement was obtained from cycle I and cycle II. It is known from the initial test that 11 students completed (34.37%) and 21 students did not complete (65.62%) with an average score of 55.21, in cycle I there were 17 students who completed (53.12%) and 15 students incomplete (46.87%) with an average value of 60.41, and in cycle II there were 28 students who completed (87.50%) and 4 students did not complete (12.50%) with an average value of 76.82.